Trees - Johnson, Sarah, 1980 February 16- (Themes in environmental history, 2015)
Comprising essays selected from 'Environment and History' and 'Environmental Values', the inexpensive volumes in this series address important aspects of environmental history through theoretical essays and case studies. 'Trees' addresses the roots of environmental history in forest history, offering a substantial section on forestry practice and ideology and the power-relations that have been and continue to be played out in global forests.